Price Linkages within Selected Vegetable Markets in Malaysia - Mohamed, Zainal Abidin; Mohd. Arshad, Fatimah; Hashim, Sharifah (Universiti Putra Malaysia Press, 1996)
This study examined the nature of price linkages in farm, wholesale and retail markets of eleven selected Malaysian vegetables, and focused on the lead-lag relationship in vertical level within the selected markets. The statistical tests used for the causality and lead and lag relationship were based on methods developed by Granger, Haugh and Pearce. Findings indicate that price discovery is made at the wholesale centre and whole sale price appears to lead both farm and retail prices for most of the vegetables examined.